Noninvasive Detection of a Ruptured Aneurysm at a Basilar Artery Fenestration with Submillimeter Multisection CT Angiography - Cademartiri, Filippo; Stojanov, Dragan; Dippel, Diederik W.J.; van der Lugt, Aad; Tanghe, Herve (American Journal of Neuroradiology, 2003)
Summary: The criterion standard for the detection of intracranial aneurysms is digital subtraction angiography. MR imaging and CT provide good accuracy in the evaluation of brain arteries and aneurysms. We herein report a case of a ruptured aneurysm at a basilar artery fenestration. The diagnosis was assessed with 16-row multisection CT angiography and was confirmed by using digital subtraction angiography. The patient was successfully treated with coil placement.